Breast Imaging Review : A Quick Guide to Essential Diagnoses - Shah, Biren A.; Fundaro, Gina M.; Mandava, Sabala R. (Springer International Publishing : Imprint: Springer, 2015)
This book provides a concise review of essential radiology findings for interpreting multimodality images of the breast. It includes over 90 cases that present patient history, radiologic findings, common diagnoses, and discussion points, accompanied by over 360 high-quality digital images derived from mammography, ultrasound, MRI, and PET modalities. It also presents concise pearls covering the basics of interventional breast procedures; high-yield facts vital to the practice of breast imaging; and a quick reference to the fifth edition of the American College of Radiology Breast Imaging-Reporting and Data System (BI-RADS) Atlas for mammography, ultrasound, and breast MRI. Breast Imaging Review: A Quick Guide to Essential Diagnoses, 2nd Edition, is a valuable resource for radiology residents preparing to take the core and certifying exams as well as for fellows and practicing radiologists interested in reviewing the basics of breast imaging interpretation and interventional procedures.